Gambaran Proses Adaptasi Mahasiswa Baru STIKES di Surabaya - Ni Nyoman Wahyu Lestarina; Dwi Purwantini (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT New students are faced with different situations when entering lectures at tertiary institutions. This makes the adaptation process for new students more difficult. At the time of entering college, new students are faced with being able to improve their ability to adapt and be able to adapt to the environment in college. Good adaptation helps students to cope with educational and academic demands.This study’s aim is to see an overview of adaptation in tertiary institutions, especially for new students. The research design used is descriptive. The population of this study was new STIKES students in Surabaya with a total sample of 68 people who were taken by purposive sampling technique. The measuring tool used is the Student Adaptation College Questionnaire (SACQ). The research was conducted in February 2022. The research results obtained from the four aspects of student adaptation found that 54.4% had low academic adjustment aspects, 63.2% had low social adjustment aspects, 63.2% had high personal-emotional adjustment aspects, and 54.4% had low institutional attachment aspects. New STIKES students in Surabaya have low scores on the aspects of academic adjustment, social adjustment, and institutional adjustment. There needs to be intensive guidance for new students through a mentoring program by both supervisors and student organizations. Keywords: Adaptation, New Student  ABSTRAK Mahasiswa baru dihadapkan pada situasi yang berbeda saat memasuki perkuliahan di perguruan tinggi. Hal ini membuat membuat proses adaptasi mahasiswa baru menjadi lebih sulit. Pada saat memasuki perguruan tinggi, mahasiswa baru dihadapkan untuk dapat meningkatkan kemampuan dalam penyesuaian diri dan mampu beradaptasi dengan lingkungan di perguruan tinggi. Adaptasi yang baik membantu mahasiswa untuk mengatasi tuntutan pendidikan dan akademik. Tujuan penelitian ini adalah untuk melihat gambaran adaptasi di perguruan tinggi terutama bagi mahasiswa baru. Desain penelitian yang digunakan adalah deskriptif. Populasi penelitian ini adalah mahasiswa baru STIKES di Surabaya dengan jumlah sampel 68 orang yang diambil dengan teknik sampling purposive sampling. Alat ukur yang digunakan adalah Student Adaptation College Questionnaire (SACQ). Penelitian dilakukan pada bulan Februari 2022. Hasil penelitian didapatkan dari keempat aspek pada adaptasi mahasiswa didapatkan bahwa 54,4% mahasiswa memiliki aspek academic adjustment yang rendah, 63,2% mahasiswa memiliki aspek social adjustment yang rendah, 63,2% mahasiswa memiliki aspek personal- emotional adjustment tinggi dan 54,4% mahasiswa memiliki aspek institutional attachment yang rendah. Mahasiswa baru STIKES di Surabaya memiliki nilai rendah pada aspek academic adjustment, social adjustment dan institutional adjustment. Perlu adanya bimbingan intensif pada mahasiswa baru melalui program bimbingan baik oleh dosen pembimbing maupun organisasi mahasiswa. Kata Kunci: Adaptasi, Mahasiswa Baru